Neutrophil extracellular trap formation is regulated by CXCR2 in COPD neutrophils. Issue 4 (12th April 2018) - Pedersen, Frauke; Waschki, Benjamin; Marwitz, Sebastian; Goldmann, Torsten; Kirsten, Anne; Malmgren, Anna; Rabe, Klaus F.; Uddin, Mohib; Watz, Henrik
Chronic obstructive pulmonary disease (COPD) is characterised by persistent neutrophilic inflammation of the airways, which is associated with enhanced neutrophil extracellular trap (NET) formation of airway neutrophils [1–3]. NETs are web-like extracellular structures consisting of neutrophil DNA components and degradative enzymes ( e.g. neutrophil elastase and myeloperoxidase) which are released from azurophilic granules by activated neutrophils [4]. Initially found to immunoregulate host defence responses during bacterial infections, emerging data indicate that exaggerated NET formation and/or delayed NET clearance may inflict tissue damage and organ dysfunction in a range of human inflammatory diseases independent of infections [5, 6]. Recently, we found NET formation of sputum neutrophils and extracellular DNA levels in sputum supernatant to be significantly enhanced in patients with stable COPD irrespective of the current smoking state or the purulence of the sputum samples [1]. Several studies, including our own, show that the amount of NET formation and/or level of extracellular DNA in patients with stable COPD correlate with the airflow limitation, suggesting that NET formation by airway neutrophils may contribute to the lung tissue damage observed in COPD [1–3]. However, the underlying mechanisms inducing NET formation in COPD neutrophils are largely unexplored. Furthermore, it is unknown whether neutrophils undergo NETosis following migration into the lung tissues or whether neutrophils are constitutively poised to undergo this response in circulation during COPD-related inflammation. It is notable that there is an increase in the release of cell-free DNA and myeloperoxidase that are active constituents of NETs in peripheral blood in COPD patients [7–9]. Here, we aimed to compare NET formation in autologous neutrophils derived from peripheral blood and sputum from COPD patients ex vivo . We also investigated whether the selective CXCR2 antagonist AZD5069, that has been shown to block trafficking of neutrophils from blood into airways in bronchiectasis patients [10] and more recently in a small cohort of neutrophilic asthma patients [11], could dampen NET formation in COPD-derived neutrophils ex vivo . CXCR2 might have a crucial role in neutrophil extracellular trap formation in COPD neutrophils http://ow.ly/LRst30iE1Bw